2016
DOI: 10.1007/s11284-016-1356-9
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of arbuscular mycorrhizal fungi in the drawdown zone of the Three Gorges Reservoir under different fertilization histories

Abstract: Impoundment of the Three Gorges Reservoir (TGR) has dramatically influenced the riparian environment and shaped a new drawdown zone, which has experienced long‐term winter conditions and short periods of summer flooding. The community structure and diversity of arbuscular mycorrhizal (AM) fungi (AMF) were investigated in three areas with different fertilization histories [Area A (5 years of fertilization), Area B (3 years of fertilization) and Area C (no fertilization)] in the drawdown zone of the TGR. Altoget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
(77 reference statements)
2
4
0
Order By: Relevance
“…The latter genus was only detectable within the ITS1 dataset and represented by two OTUs. A more recent study reported similar results [ 73 ]. Among areas with three different fertilization intensities for restoration of local plant communities, they also found Glomus and Funneliformis being the most predominant genera.…”
Section: Discussionsupporting
confidence: 76%
“…The latter genus was only detectable within the ITS1 dataset and represented by two OTUs. A more recent study reported similar results [ 73 ]. Among areas with three different fertilization intensities for restoration of local plant communities, they also found Glomus and Funneliformis being the most predominant genera.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, the use of molecular tools for identifying communities of AM fungi has been development. However, since there is still absence of uni- formity regarding the AMF-specific primer system that best reflect the diversity of AM fungi in a community (Kohout et al 2014), we decided to use the morphological characterization since we believe this approach remains valid to reach the aim of this study, as has been pointed out by other authors (v.g., Oehl et al 2004, Luo et al 2016.…”
Section: Spores Of Arbuscular Mycorrhizal Fungimentioning
confidence: 99%
“…Interestingly, the population of the stoloniferous and rhizomatous C. dactylon, a widely distributed flooding-tolerant C 4 that is perennial in the drawdown zone of the TGR, has increased under the prolonged submergence and drying-wetting cycles since 2010 [23]. Apart from a strong growth performance, C. dactylon has shown high AMF colonization (15-54%) [23], which might contribute to improved vegetation restoration in the anti-seasonal drawdown zones of TGR [24]. Although the diversity and distribution patterns of AMF communities have been investigated in TGR [24] and wetlands [25][26][27][28][29], the responses of the AMF community of flooding-tolerant plants, including C. dactylon, to changes in soil property and land-use types under the drying-wetting alternations are still poorly understood.…”
mentioning
confidence: 99%
“…Apart from a strong growth performance, C. dactylon has shown high AMF colonization (15-54%) [23], which might contribute to improved vegetation restoration in the anti-seasonal drawdown zones of TGR [24]. Although the diversity and distribution patterns of AMF communities have been investigated in TGR [24] and wetlands [25][26][27][28][29], the responses of the AMF community of flooding-tolerant plants, including C. dactylon, to changes in soil property and land-use types under the drying-wetting alternations are still poorly understood. Moreover, limited information is available if AMF occurrence and functioning are different between soils and roots, particularly under contrasting land-use changes [24,26].…”
mentioning
confidence: 99%
See 1 more Smart Citation